Bite and tooth marks on sauropod dinosaurs from the Morrison Formation - Lei, Roberto (2023)
Funding Information: Christophe Hendrickx was funded by the Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET) and Agencia Nacional de Promoción Científica y Tecnológica, Argentina to Christophe Hendrickx (Beca Pos-doctoral CONICET Legajo 181417). Emanuel Tschopp held a Theodore Roosevelt Memorial Fund and Division of Paleontology Postdoctoral Fellowship provided by Richard Gilder Graduate School at the American Museum of Natural History, New York, during the course of this work at AMNH, and currently holds a Alexander von Humboldt Fellowship for Experienced Researchers. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. Funding Information: The following grant information was disclosed by the authors: The Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET). Agencia Nacional de Promoción Científica y Tecnológica, Argentina to Christophe Hendrickx (Beca Pos-doctoral CONICET Legajo ): 181417. Emanuel Tschopp held a Theodore Roosevelt Memorial Fund and Division of Paleontology Postdoctoral Fellowship provided by Richard Gilder Graduate School at the American Museum of Natural History, New York. Publisher Copyright: Copyright 2023 Lei et al.